2021
DOI: 10.1080/11356405.2021.1905957
|View full text |Cite
|
Sign up to set email alerts
|

Academic staff attitudes and barriers to integrating sustainability in the curriculum at Spanish universities (Actitudes del profesorado y barreras a la sostenibilización curricular en la universidad española)

Abstract: The literature on integrating sustainability in higher education curricula has identified a series of circumstances that can hinder or slow down the transition towards education for sustainable development. This article assesses the influence of two of these circumstances in Spanish universities: teachers' insufficient support for the principles and objectives of sustainable development and their reluctance to consider conveying values as part of their teaching duties. The article collects evidence from the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…An easy and frequent option is to blame the disinterest of the teachers. However, previous surveys [66] conclude that the majority of university teachers in Spain are in favour of the incorporation of sustainability into their subjects. With respect to the responsibility of the university institutions themselves, we have already referred to their loosely coupled nature and the limited efficacy with which their management bodies influence teaching.…”
Section: Discussionmentioning
confidence: 93%
“…An easy and frequent option is to blame the disinterest of the teachers. However, previous surveys [66] conclude that the majority of university teachers in Spain are in favour of the incorporation of sustainability into their subjects. With respect to the responsibility of the university institutions themselves, we have already referred to their loosely coupled nature and the limited efficacy with which their management bodies influence teaching.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, the fact that justice, equity and the circular economy appear to be more frequently mentioned by women may be related to their more favorable attitude toward including sustainability in the curriculum (Olaskoaga-Larrauri et al., 2021), as well as their greater social awareness as an oppressed group resulting from the power relations established in the patriarchal system (Eizenberg and Jabareen, 2017;Kowalczuk, 2021). Another possible reason why this representation appears to be associated with women could be the high feminization of the social sciences area, as women continue to predominate in fields such as health sciences, social sciences or education, while men are more strongly associated with careers involving basic sciences, technology and engineering (Acuña Salazar et al, 2022).…”
Section: The Representation Of Sustainabilitymentioning
confidence: 99%
“…Therefore, the inclusion of sustainability in the university is shaped by important factors such as the faculty's conception of sustainability and the training of teachers in this area (Solís-Espallargas et al, 2019). As previous research shows, there is a strong relationship between teachers' perception of the importance of sustainability and their willingness to integrate this concept (Olaskoaga-Larrauri et al, 2021) and between prior training on sustainability and its inclusion in teaching (Moreno-Pino et al, 2022). We understand their representations of sustainability as having four fundamental functions, namely, a knowledge function, enabling understanding and communication; an orientation function, guiding behavior and practices; a legitimization function, justifying positions and behavior; and an identity function, enabling social groups to define their identity (Serrano Oswald, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some universities are committed to changing the curriculum by including new modules to strengthen content related to sustainable development [31] and stressing extension of the sustainable development curriculum [32,33]. However, studies have shown that they provide insufficient support for the principles and goals of sustainable development [34,35].…”
Section: Studies On the Universities' Activities For Sustainable Deve...mentioning
confidence: 99%